2008 IEEE International Conference on Global Software Engineering 2008
DOI: 10.1109/icgse.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Empirical Research in Global Software Engineering: A Classification Scheme

Abstract: Increased popularity of global software engineering (GSE) has resulted in quite a number of research and industrial studies. As the area matures, an increased focus on empirically supported results leads to a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
(17 reference statements)
0
27
0
Order By: Relevance
“…The use of visual techniques in SM, such as bubble plots, has been recommended by Petersen et al [2] and such techniques have been used to convey the results of mapping and classification studies [13] [6]. Figure 4 presents the results of this study in the form of a bubble plot.…”
Section: Bubble Plot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of visual techniques in SM, such as bubble plots, has been recommended by Petersen et al [2] and such techniques have been used to convey the results of mapping and classification studies [13] [6]. Figure 4 presents the results of this study in the form of a bubble plot.…”
Section: Bubble Plot Analysismentioning
confidence: 99%
“…We also considered the same source for the methodologies used in software engineering research. However, to better reflect the GSE perspective we also considered other methodologies [1] [13]. Hence, we added Computer Mediated Communication (CMC) analysis to cover studies that investigate artifacts such as chat-histories and emails.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…In order to ease the evaluation of applicability of the findings reported in this paper, the case study is described as suggested by [13].…”
Section: B Case Study Overviewmentioning
confidence: 99%
“…The data extraction form is used for extracting and capturing the data. We designed a data extraction form based on the items marked with (*) in Table 2 as well as some data extraction items found in [3] and [2] (such as statement of contributions to literature, stated hypothesis if any, used metrics, and study focus). The first author extracted the data from the selected papers and stored the data in a spreadsheet for analysis.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…For instance, a recent literature review of empirical research in Agile Software Development found only 36 empirical papers [2]. A higher but still limited number of empirical studies was found in [3], which reported a review of empirical research in Global Software Engineering (GSE). The researchers found 12 (18.2%) empirical papers from a set of 66 papers and posters.…”
Section: Introductionmentioning
confidence: 99%